Phosphatase Wip1 in Immunity: An Overview and Update - Shen, Xiao-Fei; Zhao, Yang; Jiang, Jin-Peng; Guan, Wen-Xian; Du, Jun-Feng (Frontiers in Immunology, 2017)
Wild-type p53-induced phosphatase 1 (Wip1) is a newly identified serine/threonine phosphatase which belongs to the PP2C family. Due to its involvement in stress-induced networks and overexpression in human tumors, primary studies have mainly focused on the role of Wip1 in tumorigenesis. It now has also been implicated in regulating several other physiological processes such as organism aging and neurogenesis. Recent evidence highlights a new role of Wip1 in controlling immune response through regulating immune cell development and function, as well as through the interplay with inflammatory signaling pathways such NF-κB and p38 MAPK. In this short review, we will give an overview of Wip1 in immunity to better understand this important phosphatase.